MANAGEMENT OF COCCIDIOSIS OUTBREAK IN TURKEY GROWERS - Henry, A. Clement Ebenezer; Jageetheesan, PN; Maheela, C; Kumar, P Senthil (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
An outbreak of coccidiosis was recorded in the forty per cent of Nandanam – II turkey growers maintained at TANUVAS – Regional Research Centre, Pudukkottai and 6.25 per cent of the affected birds died after 5 – 10 days from the onset of symptoms. The microscopic examination of superficial scraping of the mucosa from intestines and caecum of dead birds revealed the presence of large numbers of schizonts (+++) and oocysts (++) of Eimeria sp. in the caecal / intestinal contents. Coproculture for in vitro sporulation of coccidial oocyst revealed the following species; Eimeria meleagrimitis (upper small intestine) and Eimeria adenoides (caeca). The entire flocks of turkey grower were treated with anticoccidial drugs Supercox (Diaveridine and Sulphaquinoxaline) in drinking water and Amprolium hydrochloride in feed as a shuttle programme. All the affected turkey growers recovered after 7-10 days from the onset of infection and showed marked improvement in feed intake and body weight gain.
Keywords: Eimeria; Anticoccidial; Turkey; Ccoccidial oocyst